The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1016/j.chom.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Low-Abundance Biofilm Species Orchestrates Inflammatory Periodontal Disease through the Commensal Microbiota and Complement

Abstract: SUMMARY Porphyromonas gingivalis is a low-abundance oral anaerobic bacterium implicated in periodontitis, a polymicrobial inflammatory disease, and the associated systemic conditions. However, the mechanism by which P. gingivalis contributes to inflammation and disease has remained elusive. Here we show that P. gingivalis, at very low colonization levels, triggers changes to the amount and composition of the oral commensal microbiota leading to inflammatory periodontal bone loss. The commensal microbiota and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
1,065
2
19

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 955 publications
(1,165 citation statements)
references
References 50 publications
54
1,065
2
19
Order By: Relevance
“…Although it appeared logical that Actinomyces, a prominent genus in health, negatively correlated with microbial load in periodontitis, it was unexpected to find lower proportions of periodontitis-associated taxa when microbial load was high. Recent studies in mice demonstrated that, low-levels of colonization by periodontitis-associated microorganisms such as Porphyromonas gingivalis are sufficient to dysregulate innate immunity pathways, facilitate an increase in overall community biomass and trigger periodontal destruction (Hajishengallis et al, 2011). Indeed, in the current study, Porphyromonas was among the genera showing a trend negative correlation with bacterial load in periodontitis.…”
Section: Subgingival Microbiome Periodontal Destruction and Inflammasupporting
confidence: 49%
“…Although it appeared logical that Actinomyces, a prominent genus in health, negatively correlated with microbial load in periodontitis, it was unexpected to find lower proportions of periodontitis-associated taxa when microbial load was high. Recent studies in mice demonstrated that, low-levels of colonization by periodontitis-associated microorganisms such as Porphyromonas gingivalis are sufficient to dysregulate innate immunity pathways, facilitate an increase in overall community biomass and trigger periodontal destruction (Hajishengallis et al, 2011). Indeed, in the current study, Porphyromonas was among the genera showing a trend negative correlation with bacterial load in periodontitis.…”
Section: Subgingival Microbiome Periodontal Destruction and Inflammasupporting
confidence: 49%
“…Therefore, elucidating the mechanisms for the pathogenesis of NASH may be valuable for drafting prophylactic and therapeutic strategies. P. gingivalis is part of a bacterial group called the keystone, of which a small amount plays a central role in the progression of chronic periodontitis (Hajishengallis et al, 2012; Hajishengallis et al, 2011). Lipopolysaccharide and various proteases produced by P. gingivalis are known to be associated with various systemic diseases, in addition to periodontal pathogens (Seymour et al, 2007; Mikuls, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Porphyromonas gingivalis ( P. gingivalis ) is a primary causative agent of periodontitis (Socransky, Haffajee, Cugini, Smith, & Kent, 1998; Hajishengallis, Darveau, & Curtis, 2012; Hajishengallis et al, 2011), and a number of studies have detected P. gingivalis in various organs throughout the body as well as in the oral cavity; thus, it might be a risk factor for systemic diseases including cardiovascular disease, diabetes, and rheumatoid arthritis (Seymour, Ford, Cullinan, Leishman, & Yamazak, 2007; Pizzo, Guiglia, Russo, & Campisi, 2011; Figuero & Sanchez‐Beltran, 2011). A recent epidemiological study showing that P. gingivalis at high frequency was present in NAFLD/NASH patients suggested a close relationship between periodontitis and NASH (Yoneda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this hypothesis, individuals with chronic periodontal diseases would eventually establish a disturbed gut microbiome commonly seen in individuals affected by systemic inflammatory diseases. In fact, the novel pathogenesis model of periodontitis (the ‘keystone-pathogen hypothesis’) proposes that periodontal pathogens can orchestrate inflammatory periodontal disease by remodelling a symbiotic periodontal microbiota into a dysbiotic one, as demonstrated in animal model studies [43,44]. However, no clinical studies in humans have evaluated the ability of periodontal pathogens to cause a dysbiosis in the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%